Effective Utilization of Supervised Learning Techniques for Process Model Matching - Shahzad, Khurram; Mazhar, Arslaan; Mustafa, Ghulam; Aslam, Faisal (Computing and Informatics, 2020)
The recent attempts to use supervised learning techniques for process model matching have yielded below par performance. To address this issue, we have transformed the well-known benchmark correspondences to a readily usable format for supervised learning. Furthermore, we have performed several experiments using eight supervised learning techniques to establish that imbalance in the datasets is the key reason for the abysmal performance. Finally, we have used four data balancing techniques to generate balanced training dataset and verify our solution by repeating the experiments for the four datasets, including the three benchmark datasets. The results show that the proposed approach increases the matching performance significantly.